Beriš near Ljubuški (western Herzegovina) – a case study of a micro-neolithic site (Archaeologia Adriatica, 2021)
The paper presents results of the excavations conducted in 2016 at the Neolithic site of Beriš near Ljubuški (western Herzegovina). The site is characterized by modest spatiality, thin deposit, scarce settlement remains, as well as typical lithic and ceramic finds of the Middle Neolithic that in their structure illustrate all kinds of activities characteristic of spatially much bigger sites of residential character. Starting from these premises the paper discusses cultural and relative chronological dimension of the site, its specific traits among other synchronous sites and importance of a micro-site within the Neolithic as a whole in the region of the eastern Adriatic and its hinterland.
Keywords: Beriš; western Herzegovina; Middle Neolithic